Video Shot Detection Method Based on Histogram Comparison Procedure - Zakaryan, Manuk K. (Mathematical Problems of Computer Science, 2021)
Video segmentation and shot detection are the main components in automatic video indexing, archiving, editing and retrieval. For the last fifteen years a lot of techniques have been proposed some of which have reliable performances in the video processing, especially for the video cut detection, key frame extraction and browsing technique. They have a big range of usage mainly in medical diagnosis, military, retail catalog, traffic control, security, etc. In this paper we provide a comparative analysis of histogram and certain structural properties based methods for video cut detection problems. Advantages and disadvantages of the mentioned methods are shown.